2021
DOI: 10.1038/s41598-021-97340-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and prognosis of polypoidal choroidal vasculopathy with different morphologies of branching vascular network on optical coherence tomography angiography

Abstract: This study highlights the clinical features and treatment response of polypoidal choroidal vasculopathy (PCV) among three different branching vascular network (BVN) morphologies in optical coherence tomography angiography (OCTA), and further correlates the BVN features with those under fluorescent angiography (FA) and indocyanine green angiography (ICGA). In total, we reviewed 70 eyes with PCV followed up for > 12 months. OCTA, ICGA and FA images were obtained at baseline and post-treatments. BVN was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Type 2 and 3 were associated with thicker choroids and increased recurrences, while type 1 was associated with the thin choroid, drusen, and AMD-like features. Ma et al 60 found that, for most patients, type 1, 2, and 3 BNN corresponded to Type C, B, and A BNN, respectively, as described by Tan et al based on FFA and ICGA. IRC was most seen with type 1, which also had the worse BCVA both at baseline and after treatment.…”
Section: Diagnosis Through Clinical Imagingmentioning
confidence: 64%
See 1 more Smart Citation
“…Type 2 and 3 were associated with thicker choroids and increased recurrences, while type 1 was associated with the thin choroid, drusen, and AMD-like features. Ma et al 60 found that, for most patients, type 1, 2, and 3 BNN corresponded to Type C, B, and A BNN, respectively, as described by Tan et al based on FFA and ICGA. IRC was most seen with type 1, which also had the worse BCVA both at baseline and after treatment.…”
Section: Diagnosis Through Clinical Imagingmentioning
confidence: 64%
“…Huang et at 59 described three different BNN on OCTA: Type 1(trunk form, larger), type 2 (glomeruli form), and type 3 (stick form, smallest). Ma et al 60 described the effect of these patterns of BNN as seen on OCTA on treatment response and outcome in PCV. Type 2 and 3 were associated with thicker choroids and increased recurrences, while type 1 was associated with the thin choroid, drusen, and AMD-like features.…”
Section: Diagnosis Through Clinical Imagingmentioning
confidence: 99%
“…Allowing some PLs to be recognized as tangled vascular structures associated with BVNs, might also help understand the role of neovascularization in the etiology of PCV and possible implications in treatment. In addition, investigators previously used SD-OCTA to classify BVNs into different subtypes based on their morphological features, where these classification systems showed some consistency with those based on ICGA and fundus fluorescence angiography (FFA) in predicting visual prognosis [45,46]. Using SS-OCTA, BVNs can be described with more morphological patterns, such as dense, very dense (bush-shaped), loose (dead-tree-shaped), pseudopod-like, and anastomosing forms.…”
Section: Presentation Of Branching Vascular Network On Ss-octamentioning
confidence: 99%
“…Bo et al (42) defined exudative recurrence as the reappearance of IRF, SRF, or serous PED OCT, or the appearance of new subretinal or RPE hemorrhage on fundus photography. Ma et al (43) described the impact of different BNN patterns observed on OCTA on the treatment response and outcomes of PCV and found that type 2 ("Glomeruli" pattern) and type 3 ("Stick" pattern) were associated with thicker choroid and increased recurrence of PCV, while type 1 ("Trunk" pattern) was associated with thin choroid, vitelliform lesions, and AMD-like features. However, because OCTA cannot display vascular leakage, it is currently primarily used in combination with structural OCT for treatment monitoring and as a reference for recurrence treatment decisions.…”
Section: Monitoring Of Pcv Recurrencementioning
confidence: 99%